2018
DOI: 10.1038/s41588-018-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex assessment of protein variant abundance by massively parallel sequencing

Abstract: Determining the pathogenicity of genetic variants is a critical challenge, and functional assessment is often the only option. Experimentally characterizing millions of possible missense variants in thousands of clinically important genes requires generalizable, scalable assays. We describe Variant Abundance by Massively Parallel Sequencing (VAMP-seq), which measures the effects of thousands of missense variants of a protein on intracellular abundance simultaneously. We apply VAMP-seq to quantify the abundance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
504
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 387 publications
(521 citation statements)
references
References 61 publications
16
504
0
1
Order By: Relevance
“…However, if some of the BRCA1 and HRAS mutations acted via some mechanism other than by perturbing their interactions with specific binding partners (BARD1 or RasGAP, respectively), as is almost certainly the case, this can explain the relative underperformance of the DMS data: it simply is not suited to identify some pathogenic mutations. The phenotypic screen for PTEN measures protein abundance in the cell by fluorescence of EGFP bound to the protein (17). This technique called VAMP-seq identifies thermodynamically unstable variants; however, this may fail to capture disease mechanisms acting through interaction disruption and loss or gain of function unrelated to destabilisation.…”
Section: Identification Of Pathogenic Human Mutations Using Dms Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, if some of the BRCA1 and HRAS mutations acted via some mechanism other than by perturbing their interactions with specific binding partners (BARD1 or RasGAP, respectively), as is almost certainly the case, this can explain the relative underperformance of the DMS data: it simply is not suited to identify some pathogenic mutations. The phenotypic screen for PTEN measures protein abundance in the cell by fluorescence of EGFP bound to the protein (17). This technique called VAMP-seq identifies thermodynamically unstable variants; however, this may fail to capture disease mechanisms acting through interaction disruption and loss or gain of function unrelated to destabilisation.…”
Section: Identification Of Pathogenic Human Mutations Using Dms Datamentioning
confidence: 99%
“…DMS experiments allow direct identification of damaging human variants in a high-throughput manner (16,17). It is likely that the effects on function derived from DMS experiments will be better indicators of the clinical effect of mutations than any computational predictors.…”
Section: Introductionmentioning
confidence: 99%
“…(B) The functional PAH tetramer and a monomer illustrating the distribution of our selected variants across the structure (PDB: 5DEN). (C) Biophysical calculations with FoldX estimate the effect of each possible single amino acid change on protein stability (ΔΔG), with the results for residues 30-70 shown here, and those for all 420 structural-resolved residues available in the Supporting Information protein function, for example, by changes in the active or cofactorbinding sites, it has been shown that, in general, most missense variant proteins are less structurally stable than the corresponding wild-type protein (Matreyek et al, 2018;Tokuriki, Stricher, Schymkowitz, Serrano, & Tawfik, 2007). Thus, a likely mechanism for the loss of function of many missense variants is loss of stability (Casadio, Vassura, Tiwari, Fariselli, & Luigi, 2011;Yue, Li, & Moult, 2005), leading to increased proteasomal degradation and thus insufficient amounts of PAH protein.…”
Section: Computational Saturation Mutagenesis and Thermodynamic Stabimentioning
confidence: 99%
“…While typical functional assays cited as evidence in variant curations analyze relatively few variants [Kanavy, et al, submitted], new multiplexed assays can analyze thousands of variants in a single experiment [26][27][28]. This kind of increased throughput facilitates the reproducibility, replication, and assay calibration using many definitive pathogenic and benign variant controls.…”
Section: Multiplexed Functional Assaysmentioning
confidence: 99%